Opportunities for accessibility of inaccessible heritage: international experience and the Аrmenian-Аzerbaijani conflict - Yeranyan, Nzhdeh (History and Culture, 2025)
Despite various efforts aimed at preserving cultural heritage, issues in cultural heritage management become more evident in crisis situations, especially during and after armed conflicts. In recent years in the Armenian reality, the attention of responsible institutions and specialists has been focused on the problems of cultural heritage preservation in Artsakh and border settlements of Armenia, where they are under daily risk of physical destruction. However, from a professional point of view, the problem is not only the damage to the heritage but often its physical inaccessibility, which primarily leads to a break in the connection between the community and the heritage, as well as damage to the heritage. In this article, using the example of Armenia, we discuss cases when, as a result of border changes, cultural heritage becomes inaccessible to the community. Through examining international experience and legal mechanisms, we have tried to understand the possibilities and tools for its solution.